ERA REVOLUSI INDUSTRI 4.0 DALAM DUNIA DIGITAL TEKNOLOGI PENDIDIKAN PEMBELAJARAN - Agus Defri Yando (Jurnal PROFITA : Akuntansi dan Manajemen, 2022)
This study aims to describe education in the Industrial Revolution Era in dealing with accounting fraud. In Indonesia, readiness to face the challenges of education in the era of the industrial revolution 4.0 is to immediately improve the capabilities and skills of human resources through education by producing reliable operators and analysts in the field of education management as a driving force for the progress of information technology-based education in Indonesia in responding to the challenges of Industry 4.0 which continues to move rapidly. Education management policies in Indonesia currently encourage all levels of education, especially higher education, to take advantage of advances in digital technology and educational computing in the fourth industrial revolution era. Several solutions that can be implemented include, among others, the suitability of curriculum and policies in education, the readiness of human resources in utilizing ICT, optimizing the abilities of students, and developing the character of students, as well as the readiness of digital-based learning facilities and infrastructure.